2021
DOI: 10.3389/fgene.2021.680725
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Proteins SRP14 and HMGB3 Control HIV-1 Tat mRNA Processing and Translation During HIV-1 Latency

Abstract: HIV-1 Tat protein is essential for virus production. RNA-binding proteins that facilitate Tat production may be absent or downregulated in resting CD4+ T-cells, the main reservoir of latent HIV in people with HIV (PWH) on antiretroviral therapy (ART). In this study, we examined the role of Tat RNA-binding proteins on the expression of Tat and control of latent and productive infection. Affinity purification coupled with mass spectrometry analysis was used to detect binding partners of MS2-tagged tat mRNA in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…More recently, it was shown that several RNA binding proteins can regulate Tat RNA processing and translation by binding to an RNA regulatory element (referred to as Tat IRES modulator of tat mRNA (TIM TAM)) present in Tat-containing transcripts. This study showed that host RNA binding proteins SRP14 (splicing regulator) and HMGB3 bind TIM TAM and modulate Tat gene expression and function and can act as positive (SRP14) or negative (HMGB3) regulators of HIV-1 viral production ( Figure 2A ) ( Khoury et al., 2021 ). Recent transcriptomics and proteomics studies have also identified several putative splicing regulators in reactivation of HIV-1 latency (see section 2).…”
Section: Co and Post-transcriptional Regulation Of Hiv-1 Gene Express...mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was shown that several RNA binding proteins can regulate Tat RNA processing and translation by binding to an RNA regulatory element (referred to as Tat IRES modulator of tat mRNA (TIM TAM)) present in Tat-containing transcripts. This study showed that host RNA binding proteins SRP14 (splicing regulator) and HMGB3 bind TIM TAM and modulate Tat gene expression and function and can act as positive (SRP14) or negative (HMGB3) regulators of HIV-1 viral production ( Figure 2A ) ( Khoury et al., 2021 ). Recent transcriptomics and proteomics studies have also identified several putative splicing regulators in reactivation of HIV-1 latency (see section 2).…”
Section: Co and Post-transcriptional Regulation Of Hiv-1 Gene Express...mentioning
confidence: 99%
“…In summary, mechanisms that control HIV-1 latency and latency reactivation include regulation of HIV-1 vRNA splicing by modulating the binding of host spliceosome complex factors to nascent HIV-1 vRNA or by acting on HIV-1 vRNA regulatory elements ( Erkelenz et al., 2015 ; Khoury et al., 2018 ; Kyei et al., 2018 ; Yukl et al., 2018 ; Norton et al., 2019 ; Telwatte et al., 2019 ; Khoury et al., 2021 ).…”
Section: Co and Post-transcriptional Regulation Of Hiv-1 Gene Express...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, PCBP1/2 along with hnRNPK have been shown (87, 89) to stimulate IRES-mediated translation of c-myc mRNA in vitro in rabbit reticulocyte lysates. Other proteins from our analysis like SRSF1 (90), SRSF6 (94), YTHDC2 (95), NCL (96, 97), IGF2BP1 (98), SRP14(99), RBM4 (100, 101) have also been shown to activate translation of their cognate mRNAs. Conversely, other proteins from our data like DDX21 (102) and hnRNPK (103) have been shown to inhibit viral IRESs and negatively regulate translation in vivo in mammalian cell lines.…”
Section: Discussionmentioning
confidence: 80%
“…HMGB1 binds RNA in vivo with an identified motif of 5 0 -MWGRA-3 0 (M = A/C, W = A/U, R = A/G; Sofiadis et al, 2021). From the same subfamily as HMGB1, HMGB3 binds to specific sites within HIV-1 Tat mRNA, including stem loops and internal bulges (Khoury et al, 2021). Many nonhuman HMGBs also bind RNA in vitro (Table 2).…”
Section: Hmgb Proteinmentioning
confidence: 99%